Desenvolvimento de vestuário para mulheres de baixa estatura - Felisbino, Fernanda (2013)
The present work searches new alternatives clothing for the consumer public fashion of low stature. This way, it seeks to confirm with a survey conducted by means of anthropometric measure and questionnaire, which exists in a certain way this problem to the public statement. With this result, it was aimed to build a table of measurements, which can benefit companies to reduce the waste of raw material and consequently the cost of the final product to the consumer, with a suitable product to biotype body without needing adjustments. This work seeks new alternatives in certain parts of clothing, to serve the specifications requested, respecting the aesthetics of public chosen with the current trends that demands a body more elongated.